The role of intercellular mediators in the regulation of reparative processes of chronic wounds when using photobiomodulation therapy - Pavlov, Sergey; Babenko, Nataliia; Kumetchko, Marina; Litvinova, Olga; Semko, Nataliia; Valilshchykov, Mykyta (Bangladesh Journal of Medical Science, 2022)
Objective: The treatment of chronic wounds is one of the actual problems in medicine. Photobiomodulation (PBM) has gained considerable recognition among treatment modalities for various medical problems including wound repair processes. This research aims to investigate the role of intercellular mediators in the regulation of reparative processes of chronic wounds with the PBM therapy in the experiment. Methods: Studies were performed on 12 Wistar rats weighing 250 ± 30g. Rats were used for modeling a chronic wound. Animals were divided into two groups: control and experimental.The animal wounds from the experimental group were treated with low-intensity laser radiation from “Lika-therapist М” in continuous mode using a wavelength of 660 nm, output power at 50 mWt, energy density at 1 J/cm² once per day for 5 days. On the 14th day after the application of wounds, 6 rats from each group were removed from the experiment. PBM efficiency was evaluated with intercellular mediators analysis, as well as with histological examination. ELISA serum analysis was done for quantifying interleukin- 1β (IL-1β), tumor necrosis factor alpha (TNF-α), interleukin-4 (IL-4), interleukin-6 (IL-6), interleukin-10 (IL-10) and granulocyte macrophage colony stimulating factor (GM-CSF). Statistical processing of the results was performed using the Statistica 6.0 analysis package. Result: PBM effect on the expression of intercellular mediators in blood serum of animals with chronic wounds after 14 days after wound modeling, showed: increase of cytokine IL-1β (p > 0,05) and IL-4 (p < 0,05) levels; decrease of TNF-α and IL-10 levels (p < 0,05); without significant changes were concentrations IL-6 and GM-CSF. The histological study showed decrease vascular count and better organization of collagen fibers in experimental group. Conclusion: Histological studies of wound healing revealed an earlier transition of the process to the remodeling phase with the use of PBM therapy. PBM therapy can be an instrument for optimizing the reparative process by correcting the regulation by intercellular mediators. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 398-403